Low risk of invasive lobular carcinoma of the breast in carriers of BRCA1 (hereditary breast and ovarian cancer) and TP53 (Li‐Fraumeni syndrome) germline mutations. Issue 1 (9th November 2018) - Ditchi, Yoan; Broudin, Chloé; El Dakdouki, Yolla; Muller, Marie; Lavaud, Pernelle; Caron, Olivier; Lejri, Donia; Baynes, Caroline; Mathieu, Marie‐Christine; Salleron, Julia; Benusiglio, Patrick R.
Abstract: Background: Invasive lobular carcinoma (ILC) of the breast has epidemiological, molecular and clinical specificities, and should likely be considered a unique entity. As for genetic susceptibility, CDH1 germline mutations predispose exclusively to ILC . Data are however scarce regarding ILC in women with BRCA1/2 (Hereditary Breast and Ovarian Cancer) and TP53 (Li‐Fraumeni syndrome) germline mutations . Methods: We included all breast cancers from female patients tested at our institute between 1992 and 2016 (n = 3469) for which pathology data were available. ILC proportion comparison according to mutational status was performed by a chi‐squared test. The impact of susceptibility genes on ILC proportion was investigated by univariate logistic regression with wild‐type patients as reference. Results and discussion: There were 265 (7.64%) ILC: 2/342 (0.58%) in BRCA1 patients, 24/238 (10%) in BRCA2 patients, 1/57 (1.75%) in TP53 patients and 238/2832 (8.4%) in non‐carriers. The majority of breast cancers in all groups were invasive ductal and ductal in situ carcinomas. The difference in ILC proportion was highly significant ( P  < 0.001). Compared to wild‐type patients, BRCA1 was associated with a lower ILC proportion (OR 0.064 [95% CI 0.016;0.259], P  < 0.0001). BRCA2 OR was 1.222 [95%CI 0.785;1.902] ( P  = 0.374), TP53 OR was 0.195 [95%CI 0.027;1.412] ( P  = 0.105). ILC are therefore underrepresented in BRCA1 and TP53 mutation carriers. Formal significance ( P  = 0.05) was not reached for TP53, but statistical power was only 38%. Based on ILC incidence in the general population, we make the hypothesis that BRCA1 and TP53 do not predispose to ILC, as the few occurrences of ILC in mutation carriers could be attributed to chance and not to germline mutations. Our observations will be useful to clinical cancer geneticists managing patients with ILC, as a BRCA1 or TP53 mutation in these patients would be unlikely. Genetic counseling should be adapted accordingly.